Rare earth zirconate / MAX phase carbide composite ceramic and preparation method thereof
By combining MAX phase carbide with rare earth zirconate, rare earth zirconate/MAX phase carbide composite ceramics are prepared, which solves the problem of insufficient thermal expansion coefficient and fracture toughness of rare earth zirconate ceramic materials at high temperatures, and achieves better thermal physical properties and resistance to CMAS corrosion.
Patent Information
- Application Number
- CN202411754370.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
Rare earth zirconate ceramic materials have a small thermal expansion coefficient and poor fracture toughness at high temperatures, which limits their application in high-temperature gas inlet temperatures before turbines of advanced aircraft engines.
By combining MAX phase carbide with rare earth zirconate, a rare earth zirconate/MAX phase carbide composite ceramic is prepared to improve its thermal physical properties and mechanical properties.
It improves the thermal physical properties and resistance to CMAS corrosion of composite ceramics, has low thermal conductivity and high fracture toughness, and is suitable as a new thermal barrier coating material.
Smart Images

Figure CN119569449A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic non-high temperature composite ceramic materials, and in particular relates to a rare earth zirconate / MAX phase carbide composite ceramic and a preparation method thereof. Background Art
[0002] At present, the traditional yttria-stabilized zirconia (YSZ) thermal barrier coating materials have been unable to adapt to the continuous increase in the gas inlet temperature (>1300℃) before the turbine of advanced aircraft engines, and the development of new thermal barrier coating materials is imminent. The general formula of rare earth zirconate materials is RE2Zr2O7 (RE = rare earth element), which mainly has pyrochlore structure and defective fluorite structure. Compared with traditional YSZ, the rare earth zirconate crystal structure has a relatively high oxygen vacancy concentration, which increases phonon scattering and has lower thermal conductivity. Rare earth zirconates are considered to be a type of thermal barrier coating ceramic layer material with great application prospects because of their advantages such as higher melting point, better high-temperature phase stability and lower thermal conductivity. However, compared with traditional YSZ phase thermal barrier coatings, rare earth zirconates have disadvantages such as smaller thermal expansion coefficient and poor fracture toughness, which directly affect the service life of the coating.
[0003] In order to further improve the thermophysical properties and fracture toughness of rare earth zirconates, current research is mainly focused on doping and modification. As far as rare earth zirconates are concerned, doping with impurities will introduce defects, thereby "relaxing" the lattice, reducing the lattice energy, and achieving the purpose of increasing the thermal expansion coefficient. Similarly, doping with impurities can also change the crystal structure, thereby achieving a toughening effect.
[0004] For example, Lehmann et al. (Thermal conductivity and thermal expansion coefficients of the lanthanum rare-earth-element zirconate system. J Am Ceram Soc, 2003, 86(8):1338-1344) used La2Zr2O7 as the starting material and used trivalent rare earth elements Nd, Eu, Gd and Dy to replace part of La in the raw material to prepare La2Zr2O7. 1.4 Nd 0.6 Zr2O7、La 1.4 Eu 0.6 Zr2O7、La 1.4 G 0.6 Zr2O7 and La 1.7 Dy 0.3 Zr2O7 bulk materials, and found that the thermal conductivity of these materials is lower than that of pure La2Zr2O7 at temperatures below 1000°C, especially La 1.4 Nd 0.6The thermal conductivity of Zr2O7 is 0.90 W·m at 800℃ -1 ·K -1 , which is significantly lower than the 1.55 W·m of La2Zr2O7 at the same temperature. -1 ·K -1 . ZHOU et al. (Preparation and thermophysical properties of CeO2 dopedLa2Zr2O7 ceramic for thermal barrier coatings. J Alloys Compd, 2007, 2007, 438 (1-2): 217-221) showed that the thermal expansion coefficient of La2Zr2O7 was significantly improved by CeO2 doping, and increased with the increase of temperature. When the temperature exceeded 400°C, it was significantly higher than the thermal expansion coefficient of undoped La2Zr2O7 and YSZ at the same temperature. Guo et al. (Thermal expansion and fracture toughness of (RE 0.9 Sc 0.1 )2Zr2O7(RE=La,Sm,Dy,Er)ceramics,Ceramics International,2016,42(1):583)Research(RE 0.9 Sc 0.1 )2Zr2O7(RE=La,Sm,Dy,Er) ceramics found Sc 3+ In (La 0.9 Sc 0.1 )2Zr2O7 and (Sm 0.9 Sc 0.1 )2Zr2O7 is an interstitial ion in the unit cell, the unit cell expands, and the lattice parameter increases. 0.9 Sc 0.1 )2Zr2O7 and (Er 0.9 Sc 0.1 )2Zr2O7 replaces RE in the unit cell 3+ ions, unit cell shrinkage; Sc 3+ The introduction of causes lattice distortion and increases the cohesive energy (RE 0.9 Sc 0.1 )2Zr2O7 have improved fracture toughness, and the fracture toughness of Gd2Zr2O7 (1.4MPa·m 1 / 2 ) has the most significant toughening effect, because Sc 3+The introduction of also induces phase change in Gd2Zr2O7, which absorbs fracture energy; Wang et al. (Enhanced thermal expansion and fracture toughness ofSc2O3-doped Gd2Zr2O7ceramics, Ceramics International, 2015, 41, 10730-10735.) reported that doping Sc2O3 in Gd2Zr2O7 introduces lattice defects and structural disorder, which enhances toughness but also leads to a decrease in thermal expansion coefficient. In addition to doping modification, ceramic materials can also be selected as the second phase to form a composite ceramic structure combined with a ceramic matrix to improve fracture toughness. For example, Wang Caimei et al. ("Lanthanum phosphate / gadolinium zirconate composite material and its coating research", Tianjin University, 2017.) also discloses the introduction of the second phase lanthanum phosphate to modify the performance of Gd2Zr2O7. Although the fracture toughness of the material is effectively increased, the effect on the thermal expansion coefficient is not mentioned.
[0005] From the above, we can see that although rare earth zirconate has lower thermal conductivity, better phase stability and sintering resistance than YSZ ceramic materials, the thermal expansion coefficient and fracture toughness of rare earth zirconate are not as high as those of YSZ ceramic materials, which limits the use of rare earth zirconate ceramic materials. Therefore, it is of great significance to develop rare earth zirconate ceramic materials with higher thermal expansion coefficient and fracture toughness. Summary of the invention
[0006] Based on the above technical problems, the present invention provides a rare earth zirconate / MAX phase carbide composite ceramic and a preparation method thereof. By composite-modifying the rare earth zirconate with MAX phase carbide, not only the thermal physical properties and mechanical properties of the obtained composite ceramic are improved, but also its anti-CMAS corrosion effect is improved, laying a foundation for the research and development of new thermal barrier coating materials.
[0007] The present invention provides a rare earth zirconate / MAX phase carbide composite ceramic, wherein the composite ceramic comprises rare earth zirconate and MAX phase carbide in a weight ratio of 9:1-1:9;
[0008] The rare earth zirconate is Yb-doped gadolinium zirconate Gd (Gd x Yb 1-x )2Zr2O7, 0<x<1; the MAX phase carbide is MAX phase M2AlC, M=VB group or VIB group element.
[0009] Preferably, x=0.9.
[0010] Preferably, M = Ta or Cr.
[0011] The present invention also provides a method for preparing a rare earth zirconate / MAX phase carbide composite ceramic, comprising: mixing rare earth zirconate powder and MAX phase carbide powder in a weight ratio of 9:1-1:9, pressing, and sintering to obtain the rare earth zirconate / MAX phase carbide composite ceramic.
[0012] Preferably, the rare earth zirconate powder is obtained by mixing gadolinium oxide, zirconium oxide and ytterbium oxide and sintering;
[0013] Preferably, the molar ratio of gadolinium oxide, zirconium oxide and ytterbium oxide is 0.9:2:0.1.
[0014] Preferably, the mixing is achieved by wet ball milling;
[0015] Preferably, during wet ball milling, anhydrous ethanol is used as the solvent, the ball milling speed is 150-300 r / min, and the ball milling time is 12-16 h.
[0016] Preferably, the sintering includes pre-sintering and secondary sintering;
[0017] Preferably, the pre-sintering temperature is 1300-1500° C., and the sintering time is 4-8 hours; the secondary sintering temperature is 1400-1600° C., and the sintering time is 4-8 hours.
[0018] In the present invention, after pre-sintering, the obtained pre-sintered ceramic is subjected to secondary ball milling. After the secondary ball milling, the mixed powder can be evenly mixed so that it can fully react during the secondary calcination.
[0019] Preferably, the MAX phase carbide is MAX phase M2AlC, M = VB group or VIB group element;
[0020] Preferably, M = Ta or Cr.
[0021] Preferably, the mixing is also achieved by wet ball milling, and after mixing, the mixed powder is sieved through a 200-300 mesh sieve;
[0022] Preferably, during wet ball milling, anhydrous ethanol is used as the solvent, the ball milling speed is 150-300 r / min, and the ball milling time is 12-16 h.
[0023] Preferably, the pressing pressure is 10-15 MPa, and the time is 0.5-2 min; the sintering temperature is 1400-1550° C., and the time is 4-6 h.
[0024] Beneficial effects of the present invention:
[0025] (1) Compared with pure GYbZ, the GYbZ / TAC and GYbZ / CAC composite ceramics of the present invention have better thermophysical properties and good resistance to CMAS corrosion, among which 0.8GYbZ / 0.2TAC has the best thermophysical properties.
[0026] (2) Among the GYbZ / TAC and GYbZ / CAC composite ceramics described in the present invention, the 0.8GYbZ / 0.2TAC composite ceramic has the lowest thermal conductivity, which can reach 1.438 W·m at 800°C. -1 ·K -1 , the thermal expansion coefficient at 1400℃ can reach 12.337×10 -6 K -1 , is expected to become a new type of high-temperature ceramic material.
[0027] (3) Among the GYbZ / TAC and GYbZ / CAC composite ceramics of the present invention, the 0.8GYbZ / 0.2TAC composite ceramic also has a relatively high fracture toughness, which can reach 2.12MPa·m 1 / 2 , and has high temperature phase stability.
[0028] (4) The preparation method of the GYbZ / TAC and GYbZ / CAC composite ceramics of the present invention has high process purity, low impurity content, low product preparation cost, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is the XRD pattern of the GYbZ ceramic powder prepared in Example 1;
[0030] Figure 2 is the XRD pattern of the 0.8GYbZ / 0.2TAC composite ceramic block prepared in Example 1;
[0031] Figure 3 is a thermal conductivity diagram of the 0.8GYbZ / 0.2TAC composite ceramic block prepared in Example 1;
[0032] Figure 4 is a thermal expansion coefficient diagram of the 0.8GYbZ / 0.2TAC composite ceramic block prepared in Example 1;
[0033] Figure 5 is a graph of fracture toughness and hardness of the 0.8GYbZ / 0.2TAC composite ceramic block prepared in Example 1;
[0034] Figure 6 is a DSC curve diagram of the 0.8GYbZ / 0.2TAC composite ceramic block prepared in Example 1;
[0035] Figure 7The CMAS (33CaO-9MgO-13AlO) of the 0.8GYbZ / 0.2TAC composite ceramic block prepared in Example 1 1.5 -45SiO2) corrosion cross section.
[0036] Figure 8 This is the SEM surface morphology of the 0.8GYbZ / 0.2TAC composite ceramic block prepared in Example 1. DETAILED DESCRIPTION
[0037] Hereinafter, the present invention will describe the technical solution in detail through specific embodiments, but it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0038] Example 1
[0039] This embodiment provides a rare earth zirconate / MAX phase carbide composite ceramic, whose composition is 0.8GYbZ / 0.2TAC; the preparation method of the 0.8GYbZ / 0.2TAC composite ceramic comprises the following steps:
[0040] (1) 10.660 g of gadolinium oxide, 8.050 g of zirconium oxide and 1.290 g of ytterbium oxide were weighed and added to a jar, 200 mL of anhydrous ethanol was poured into the mixture, and the mixture was placed in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h; the milled raw material suspension was dried at room temperature for 24 h, and then placed in a high-temperature furnace for pre-sintering at a temperature of 1400° C. for 6 h; the pre-sintered powder material was added to the jar again, 200 mL of anhydrous ethanol was poured into the mixture, and the mixture was placed in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h; the pre-sintered powder suspension was dried at room temperature for 24 h, and then placed in a high-temperature furnace for secondary sintering at a temperature of 1500° C. for 6 h. After the sintered material was evenly ground, pure GYbZ ceramic powder was obtained;
[0041] (2) Weigh 20 g of GYbZ ceramic powder and 5 g of TAC powder respectively and add them into a jar, pour 200 mL of anhydrous ethanol into the mixture, and place it in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h; dry the milled raw material suspension at room temperature for 24 h, pass it through a 200-mesh sieve, and then place it in a mold with a diameter of 15 mm for pressing at a pressure of 15 MPa and a holding time of 1 min; place the obtained molded original sheet in a high-temperature furnace for sintering at a sintering temperature of 1500°C for 6 h to obtain a 0.8GYbZ / 0.2TAC composite ceramic block, which is the composite ceramic.
[0042] The above GYbZ ceramic powder and 0.8GYbZ / 0.2TAC composite ceramic block were subjected to XRD test respectively. The results are as follows: Figure 1 , 2 As shown, refer to Figure 1 It can be seen that GYbZ is a single phase structure without other impurities, which meets the experimental requirements. Figure 2 It can be seen that only the diffraction peak of GYbZ was detected in the 0.8GYbZ / 0.2TAC composite ceramic block, and the diffraction peak of TAC was not detected.
[0043] The thermal diffusion coefficient and thermal expansion coefficient of the 0.8GYbZ / 0.2TAC composite ceramic block were tested. The results are as follows: Figure 3 , 4 As shown, refer to Figure 3 , 4 It can be seen that at 800°C, the thermal conductivity of the 0.8GYbZ / 0.2TAC composite ceramic block is 1.438 W·m -1 ·K -1 At 1400℃, the thermal expansion coefficient of 0.8GYbZ / 0.2TAC composite ceramic block is 12.337×10 -6 K -1 .
[0044] The fracture toughness and hardness of the 0.8GYbZ / 0.2TAC composite ceramic block were tested. Figure 5 As shown, refer to Figure 5 It can be seen that the fracture toughness of 0.8GYbZ / 0.2TAC composite ceramic block can reach 2.12MPa·m 1 / 2 , hardness is 13.88Gpa.
[0045] Figure 6 The DSC curve of the 0.8GYbZ / 0.2TAC composite ceramic block prepared in Example 1 is shown in FIG. Figure 6 It can be seen that there is no obvious endothermic and exothermic peak in the DSC curve of the 0.8GYbZ / 0.2TAC composite ceramic when it is heated to 1300℃, indicating that it has high-temperature phase stability and will not undergo phase change at 1300℃, which is better than YSZ.
[0046] The 0.8GYbZ / 0.2TAC composite ceramic block was subjected to CMAS (33CaO-9MgO-13AlO 1.5 -45SiO2) corrosion test for 4h, the results are as follows Figure 7 As shown, refer to Figure 7 It can be seen that the 0.8GYbZ / 0.2TAC composite ceramic block has excellent resistance to CMAS corrosion.
[0047] Figure 8The SEM surface morphology of the 0.8GYbZ / 0.2TAC composite ceramic block prepared in Example 1 is shown in FIG. Figure 8 It can be seen that the 0.8GYbZ / 0.2TAC composite ceramic block has a ferroelastic domain morphology, indicating that the introduction of TAC can increase the fracture toughness of 0.8GYbZ / 0.2TAC composite ceramics.
[0048] Example 2
[0049] This embodiment provides a rare earth zirconate / MAX phase carbide composite ceramic, whose composition is 0.5GYbZ / 0.5TAC; the preparation method of the composite ceramic comprises the following steps:
[0050] (1) 5.330 g of gadolinium oxide, 4.025 g of zirconium oxide and 0.645 g of ytterbium oxide were weighed and added to a jar, 200 mL of anhydrous ethanol was poured into the mixture, and the mixture was placed in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h; the milled raw material suspension was dried at room temperature for 24 h, and then placed in a high-temperature furnace for pre-sintering at a temperature of 1400° C. for 6 h; the pre-sintered powder material was added to the jar again, 200 mL of anhydrous ethanol was poured into the mixture, and the mixture was placed in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h; the pre-sintered powder suspension was dried at room temperature for 24 h, and then placed in a high-temperature furnace for secondary sintering at a temperature of 1500° C. for 6 h. After the sintered material was evenly ground, pure GYbZ ceramic powder was obtained;
[0051] (2) Weigh 10 g of GYbZ ceramic powder and 10 g of TAC powder respectively and add them into a jar, pour 200 mL of anhydrous ethanol into the mixture, and place it in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h; dry the milled raw material suspension at room temperature for 24 h, pass it through a 200-mesh sieve, and then place it in a mold with a diameter of 15 mm for pressing at a pressure of 10 MPa and a holding time of 1 min; place the obtained molded original sheet in a high-temperature furnace for sintering at a sintering temperature of 1500°C for 6 h to obtain a 0.5GYbZ / 0.5TAC composite ceramic block, which is the composite ceramic.
[0052] The thermal diffusivity and thermal expansion coefficient of the 0.5GYbZ / 0.5TAC composite ceramic block were tested. The thermal conductivity and thermal expansion coefficient were analyzed and calculated. At 800°C, the thermal conductivity was 1.725 W·m -1 ·K -1 At 1400℃, the thermal expansion coefficient is 12.427×10 -6 K -1 .
[0053] The fracture toughness and hardness of the 0.5GYbZ / 0.5TAC composite ceramic block were tested, and the fracture toughness can reach 2.87MPa·m 1 / 2 , hardness is 12.47Gpa.
[0054] Example 3
[0055] This embodiment provides a rare earth zirconate / MAX phase carbide composite ceramic, whose composition is 0.8GYbZ / 0.2CAC; the preparation method of the composite ceramic comprises the following steps:
[0056] (1) 10.660 g of gadolinium oxide, 8.050 g of zirconium oxide and 1.290 g of ytterbium oxide were weighed and added to a jar, 200 mL of anhydrous ethanol was poured into the mixture, and the mixture was placed in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h; the milled raw material suspension was dried at room temperature for 24 h, and then placed in a high-temperature furnace for pre-sintering at a temperature of 1400° C. for 6 h; the pre-sintered powder material was added to the jar again, 200 mL of anhydrous ethanol was poured into the mixture, and the mixture was placed in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h; the pre-sintered powder suspension was dried at room temperature for 24 h, and then placed in a high-temperature furnace for secondary sintering at a temperature of 1500° C. for 6 h. After the sintered material was evenly ground, pure GYbZ ceramic powder was obtained;
[0057] (2) Weigh 20 g of GYbZ ceramic powder and 5 g of CAC powder respectively and add them into a jar, pour 200 mL of anhydrous ethanol into the mixture, and place it in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h; dry the milled raw material suspension at room temperature for 24 h, pass it through a 200-mesh sieve, and then place it in a mold with a diameter of 15 mm for pressing at a pressure of 10 MPa and a holding time of 1 min; place the obtained molded original sheet in a high-temperature furnace for sintering at a sintering temperature of 1500°C for 6 h to obtain a 0.5GYbZ / 0.5TAC composite ceramic block, which is the composite ceramic.
[0058] The thermal diffusivity and thermal expansion coefficient of the 0.8GYbZ / 0.2CAC composite ceramic block were tested. The thermal conductivity and thermal expansion coefficient were analyzed and calculated. At 800°C, the thermal conductivity was 1.322W·m -1 ·K -1 At 1400℃, the thermal expansion coefficient is 12.682×10 -6 K -1 .
[0059] The fracture toughness and hardness of the 0.8GYbZ / 0.2CAC composite ceramic block were tested, and the fracture toughness can reach 2.05MPa·m 1 / 2 , hardness is 11.24Gpa.
[0060] Example 4
[0061] This embodiment provides a rare earth zirconate / MAX phase carbide composite ceramic, whose composition is 0.5GYbZ / 0.5CAC; the preparation method of the composite ceramic comprises the following steps:
[0062] (1) 5.330 g of gadolinium oxide, 4.025 g of zirconium oxide and 0.645 g of ytterbium oxide were weighed and added to a jar, 200 mL of anhydrous ethanol was poured into the mixture, and the mixture was placed in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h; the milled raw material suspension was dried at room temperature for 24 h, and then placed in a high-temperature furnace for pre-sintering at a temperature of 1400° C. for 6 h; the pre-sintered powder material was added to the jar again, 200 mL of anhydrous ethanol was poured into the mixture, and the mixture was placed in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h; the pre-sintered powder suspension was dried at room temperature for 24 h, and then placed in a high-temperature furnace for secondary sintering at a temperature of 1500° C. for 6 h. After the sintered material was evenly ground, pure GYbZ ceramic powder was obtained;
[0063] (2) Weigh 10 g of GYbZ ceramic powder and 10 g of CAC powder respectively and add them into a jar, pour 200 mL of anhydrous ethanol into the mixture, and place it in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h; dry the milled raw material suspension at room temperature for 24 h, pass it through a 200-mesh sieve, and then place it in a mold with a diameter of 15 mm for pressing at a pressure of 10 MPa and a holding time of 1 min; place the obtained molded original sheet in a high-temperature furnace for sintering at a sintering temperature of 1500°C for 6 h to obtain a 0.5GYbZ / 0.5TAC composite ceramic block, which is the composite ceramic.
[0064] The thermal diffusivity and thermal expansion coefficient of the 0.5GYbZ / 0.5CAC composite ceramic block were tested. The thermal conductivity and thermal expansion coefficient were analyzed and calculated. At 800°C, the thermal conductivity was 1.627W·m -1 ·K -1 At 1400℃, the thermal expansion coefficient is 12.748×10 -6 K -1 .
[0065] The fracture toughness and hardness of the 0.5GYbZ / 0.5CAC composite ceramic block were tested, and the fracture toughness can reach 2.58MPa·m 1 / 2 , hardness is 10.76Gpa.
[0066] Comparative Example 1
[0067] This comparative example proposes a rare earth zirconate ceramic, whose composition is GYbZ; the preparation method of the GYbZ ceramic comprises the following steps:
[0068] (1) 10.660 g of gadolinium oxide, 8.050 g of zirconium oxide and 1.290 g of ytterbium oxide were weighed and added to a jar, 200 mL of anhydrous ethanol was poured into the mixture, and the mixture was placed in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h; the milled raw material suspension was dried at room temperature for 24 h, and then placed in a high-temperature furnace for pre-sintering at a temperature of 1400° C. for 6 h; the pre-sintered powder material was added to the jar again, 200 mL of anhydrous ethanol was poured into the mixture, and the mixture was placed in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h; the pre-sintered powder suspension was dried at room temperature for 24 h, and then placed in a high-temperature furnace for secondary sintering at a temperature of 1500° C. for 6 h. After the sintered material was evenly ground, pure GYbZ ceramic powder was obtained;
[0069] (2) 25 g of GYbZ ceramic powder was added to a jar, 200 mL of anhydrous ethanol was poured into the mixture, and then the mixture was placed in a planetary ball mill for ball milling at a speed of 180 r / min for 14 h. The milled raw material suspension was dried at room temperature for 24 h, passed through a 200-mesh sieve, and then placed in a mold with a diameter of 15 mm for pressing. The pressing pressure was 15 MPa and the holding time was 1 min. The obtained molded original sheet was placed in a high-temperature furnace for sintering at a sintering temperature of 1500°C for 6 h to obtain a GYbZ ceramic block, namely the GYbZ ceramic.
[0070] The thermal diffusivity and thermal expansion coefficient of the GYbZ ceramic block were tested. The thermal conductivity and thermal expansion coefficient were analyzed and calculated. At 800°C, the thermal conductivity was 1.299 W·m -1 ·K -1 At 1400℃, the thermal expansion coefficient is 11.12×10 -6 K -1 .
[0071] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A rare earth zirconate / MAX phase carbide composite ceramic, characterized in that: The composite ceramic comprises rare earth zirconate and MAX phase carbide in a weight ratio of 9:1-1:9; The rare earth zirconate is Yb-doped gadolinium zirconate Gd (Gd x Yb 1-x )2Zr2O7, 0<x<1; the MAX phase carbide is MAX phase M2AlC, M=VB group or VIB group element.
2. The rare earth zirconate / MAX phase carbide composite ceramic according to claim 1, characterized in that: x=0.9。 3. The rare earth zirconate / MAX phase carbide composite ceramic according to claim 1 or 2, characterized in that: M=Ta or Cr.
4. A method for preparing a rare earth zirconate / MAX phase carbide composite ceramic, characterized in that: include: The rare earth zirconate powder and the MAX phase carbide powder are mixed in a weight ratio of 9:1-1:9, pressed, and sintered to obtain the rare earth zirconate / MAX phase carbide composite ceramic.
5. The method for preparing the rare earth zirconate / MAX phase carbide composite ceramic according to claim 4, characterized in that: The rare earth zirconate powder is obtained by mixing gadolinium oxide, zirconium oxide and ytterbium oxide and sintering. Preferably, the molar ratio of gadolinium oxide, zirconium oxide and ytterbium oxide is 0.9:2:0.
1.
6. The method for preparing the rare earth zirconate / MAX phase carbide composite ceramic according to claim 5, wherein the mixing is achieved by wet ball milling; Preferably, during wet ball milling, anhydrous ethanol is used as the solvent, the ball milling speed is 150-300 r / min, and the ball milling time is 12-16 h.
7. The method for preparing the rare earth zirconate / MAX phase carbide composite ceramic according to claim 5 or 6, wherein the sintering comprises pre-sintering and secondary sintering; Preferably, the pre-sintering temperature is 1300-1500° C., and the sintering time is 4-8 hours; the secondary sintering temperature is 1400-1600° C., and the sintering time is 4-8 hours.
8. The method for preparing the rare earth zirconate / MAX phase carbide composite ceramic according to any one of claims 4 to 7, wherein the MAX phase carbide is a MAX phase M2AlC, where M = a VB group or a VIB group element; Preferably, M = Ta or Cr.
9. The method for preparing the rare earth zirconate / MAX phase carbide composite ceramic according to any one of claims 4 to 8, wherein the mixing is also achieved by wet ball milling, and after the mixing, the mixed powder is sieved through a 200-300 mesh sieve; Preferably, during wet ball milling, anhydrous ethanol is used as the solvent, the ball milling speed is 150-300 r / min, and the ball milling time is 12-16 h.
10. The method for preparing the rare earth zirconate / MAX phase carbide composite ceramic according to any one of claims 4 to 9, wherein the pressing pressure is 10-15 MPa, the time is 0.5-2 min; the sintering temperature is 1400-1550°C, and the time is 4-6 h.
Citation Information
Patent Citations
Composite rare earth zirconate thermal barrier coating ceramic material and preparation method thereof
CN101269960A
Thermal barrier coating resistant to corrosion of molten CMAS and preparation method
CN111005024A
CMAS-corrosion-resistant self-healing thermal barrier coating and preparation method thereof
CN115074654A
Ytterbium-doped samarium zirconate cerate thermal barrier coating material as well as preparation method and application thereof
CN116143530A